2007
DOI: 10.1111/j.1600-0633.2007.00246.x
|View full text |Cite
|
Sign up to set email alerts
|

Spawning period of a southern brown trout population in a highly unpredictable stream

Abstract: –  The spawning period of brown trout (Salmo trutta L.) was studied in the river Castril, southern Spain, by means of redd counts. This mountain stream is located near to the southern limit of the species’ natural distribution range and it shows a highly unpredictable flow regime. The spawning period extended from December to mid‐April and the maximum reproductive activity was in February. These results represent the latest reproduction date and the longest spawning period reported in the literature along the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
73
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(79 citation statements)
references
References 52 publications
5
73
0
1
Order By: Relevance
“…It is highly likely that this species has relatively longer reproductive periods and two reproductive peaks in temperate waters. A similar phenomenon has been reported by Gortázar et al (2007), who demonstrated a negative correlation between reproductive duration and geographical latitude in brown trout (Salmo trutta). Callionymus ornatipinnis only spawned during a 1-h period at dusk (1730-1830 h), and spawning time was strongly associated with sunset time, but unrelated to the time of high tide.…”
Section: Discussionsupporting
confidence: 68%
“…It is highly likely that this species has relatively longer reproductive periods and two reproductive peaks in temperate waters. A similar phenomenon has been reported by Gortázar et al (2007), who demonstrated a negative correlation between reproductive duration and geographical latitude in brown trout (Salmo trutta). Callionymus ornatipinnis only spawned during a 1-h period at dusk (1730-1830 h), and spawning time was strongly associated with sunset time, but unrelated to the time of high tide.…”
Section: Discussionsupporting
confidence: 68%
“…It has also shown a wide range of variation in its reproductive traits. For instance, many authors have observed significant latitudinal variations in the mean spawning date and in the duration of the spawning period (Klemetsen et al, 2003;Gortázar et al, 2007;Larios-López et al, 2015). Furthermore, during its life cycle, brown trout migrates both long distances for spawning, and shorter ones for feeding or wintering (Klemetsen et al, 2003;Jonsson and Jonsson, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Their spawning period in the Iberian Peninsula expands from November to January (Doadrio, 2002), and occasionally until April (Gortázar et al, 2007;Larios-López et al, 2015). However, the dates and environmental triggers of the spawning movements in the Iberian Peninsula for potamodromous populations have not been sufficiently studied.…”
Section: Introductionmentioning
confidence: 99%
“…where n is the number of redds, l is the length of the reach, and s is the number of redd surveys (Baxter et al 1999;Gortazar et al 2007). We incorporated the number of surveys to allow for comparisons between years of different survey effort.…”
Section: Methodsmentioning
confidence: 99%